Triple locations of elastofibroma dorsi: First case report and review - Hassouna, Jamel B. (J Orthop, 2014)
INTRODUCTION: Elastofibroma is a rare benign fibroelastic tumor. CASE: We report a case of a 44-year-old woman, operated 4 months ago for a left infrascapular desmoid tumor and presented for bilateral mass of the left suprascapular and right infrascapular regions which were surgically resected. The diagnosis of elastofibroma was made and also confirmed for the left infrascapular desmoid tumor. Six months later, she presented an asymptomatic left infrascapular recurrence. Monitoring was continued and the patient is still asymptomatic after 24 months. DISCUSSION: We highlight the importance of imaging features understanding in order to avoid misdiagnosis and unnecessary surgical resection.